Prenatal diagnosis of fetal cardiac rhabdomyoma with severe cardiac dysfunction - Amorim, Luciane; Veras, Denilson; Júnior, Edward Araujo (Prenatal Cardiology, 2019)
Fetal cardiac tumours are rare, but rhabdomyomas are the most common. They are associated with tuberous sclerosis in 50–80% of cases. Early diagnosis of cardiac rhabdomyoma is thus important for early diagnosis of tuberous sclerosis. We describe a case of an intracardiac tumour that evolved with significant ventricular dysfunction. The report of this case teaches us an important lesson by exemplifying an unsuccessful experience of rhabdomyoma surgery.